2003
DOI: 10.1093/jn/133.6.1806
|View full text |Cite
|
Sign up to set email alerts
|

Chlorogenic Acid, Quercetin-3-Rutinoside and Black Tea Phenols Are Extensively Metabolized in Humans

Abstract: Dietary phenols are antioxidants, and their consumption might contribute to the prevention of cardiovascular disease. Coffee and tea are major dietary sources of phenols. Dietary phenols are metabolized extensively in the body. Lack of quantitative data on their metabolites hinders a proper evaluation of the potential biological effects of dietary phenols in vivo. The aim of this study was to identify and quantify the phenolic acid metabolites of chlorogenic acid (major phenol in coffee), quercetin-3-rutinosid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
317
2
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 423 publications
(339 citation statements)
references
References 39 publications
17
317
2
3
Order By: Relevance
“…Therefore, wet milling can be successfully used in order to decrease the content of free as well as esterified FA in worts. However, health-related reasons might dictate increasing the content of phenolic acids in wort and beer as these strong antioxidants are very effectively absorbed after consumption 3,6,36,41,43 .…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, wet milling can be successfully used in order to decrease the content of free as well as esterified FA in worts. However, health-related reasons might dictate increasing the content of phenolic acids in wort and beer as these strong antioxidants are very effectively absorbed after consumption 3,6,36,41,43 .…”
Section: Resultsmentioning
confidence: 99%
“…Until recently, only traces of CA and/or 5-CQA had been identified in both animal and human plasma (Lafay et al, 2006;Wittemer et al, 2005;Olthof, Hollman, Buijsman, Van Amelsvoort, & Katan, 2003;Rice-Evans, Spencer, Schroeter, & Rechner, 2000). However, currently it is known that the absorption of CGA is much higher than previously thought and studies have been shown that some individuals seem to be able to absorb up to 73% of the total of CGA ingested .…”
Section: Metabolism Absorption and Bioavailability Of Hydroxycinnamimentioning
confidence: 99%
“…It has been reported that peak plasma concentrations of phenolic acids from beer were attained 30 and 60 min after beer ingestion (73). A number of works have shown that phenolic acids are not degraded in the gastrointestinal tract prior to absorption (72)(73)(74)(75)(76)(77)(78)(79)(80)(81). Moreover, free phenolic acids are easily released from foods in the gastrointestinal tract by bacterial esterases (82) and directly absorbed, as early as in the proximal part of the small intestine (71,73).…”
Section: Phenolic Acids As Efficient Ache and Bche Inhibitorsmentioning
confidence: 99%